Sequential oral antibiotic in uncomplicated Staphylococcus aureus bacteraemia: a propensity-matched cohort analysis - Diego-Yagüe, Itziar; Mora-Vargas, Alberto; Vázquez-Comendador, Jose Manuel; Santamarina-Alcantud, Beatriz; Fernández-Cruz, Ana; Múñez-Rubio, Elena; Gutiérrez-Villanueva, Andrea; Sanchez-Romero, Isabel; Moreno-Torres, Víctor; Ramos-Martínez, Antonio; Calderón-Parra, Jorge (Support UsContactAdmin Clinical Microbiology and Infection, 2023)
Objectives: We aimed to analyse the efficacy and safety of oral sequential therapy (OST) in uncomplicated Staphylococcus aureus bacteraemia (SAB). Methods: Single-centre observational cohort at a tertiary hospital in Spain, including all patients with the first SAB episode from January 2015 to December 2020. We excluded patients with complicated SAB and those who died during the first week. Patients were classified into the OST group (patients who received oral therapy after initial intravenous antibiotic therapy [IVT]), and IVT group (patients who received exclusively IVT). We performed a propensity-score matching to balance baseline differences. The primary composite endpoint was 90-day mortality or microbiological failure. Secondary endpoints included 90-day SAB relapse. Results: Out of 407 SAB first episodes, 230 (56.5%) were included. Of these, 112 (n = 48.7%) received OST and 118 (51.3%) IVT exclusively. Transition to oral therapy was performed after 7 days (interquartile range, 4–11). The primary endpoint occurred in 10.7% (11/112) in OST vs. 30.5% (36/118) in IVT (p < 0.001). SAB relapses occurred in 3.6% (4/112) vs. 1.7% (2/118) (p 0.436). None of the deaths in OST were related to SAB or its complications. After propensity-score matching, the primary endpoint was not more frequent in the OST group (relative risk, 0.42; 95% CI, 0.22–0.79). Ninety-day relapses occurred similarly in both groups (relative risk, 1.35; 95% CI, 0.75–2.39). Discussion: After an initial intravenous antibiotic, patients with uncomplicated SAB can safely be switched to oral antibiotics without apparent adverse outcomes. This strategy could save costs and complications of prolonged hospital stays. Prospective randomized studies are needed.
Keywords: mortality; sequential oral antibiotic; Staphylococcus aureus; Scopus; JCR